Consumer Protection Against Intense Pulse Light (IPL) Treatment by Doctors at The Kusuma Beauty Clinic in Banda Aceh - Iswara, Mutiara; Sautunnida, Lia (Riviera Publishing, 2025)
Based on Article 4 Letter C of Law Number 8 of 1999 concerning Consumer Protection, consumers have the right to correct, transparent, and honest information regarding the conditions and guarantees of goods and/or services. Article 10, paragraph (3) of the Minister of Health Regulation Number 290 of 2008 concerning Approval of Medical Actions states that certain health workers can help provide explanations by their authority. However, the Kusuma Beauty Clinic doctors do not fulfill their obligations as specified in the health ministerial regulation above. This study aims to explain the implementation of Intense Pulse Light (IPL) treatment at Kusuma Beauty Clinic in Banda Aceh, the form of consumer protection against IPL treatment, and the responsibility of clinic managers for consumer losses due to IPL treatment. Empirical juridical research with qualitative analysis was used. The results show applicable regulations did not implement IPL treatment. Doctors do not provide clear explanations and informed consent to consumers. As a result, consumers suffer losses, and consumer rights are not fulfilled properly. Kusuma beauty clinic manager has offered recovery treatment. However, consumers refuse and desire money compensation worth IDR 1.651.116.800,- and the cost of psychological treatment for victims worth IDR 10.000.000.000,- as stated in decision Number 112/PDT/2023/PT BNA. Therefore, the clinic manager does not compensate the losses as consumers desire.